Thermodecomposition Kinetics of La(III) Complex with Schiff Base Ligand Derived from Glycine and O-Vanillin - GUO, FENG (Asian Journal of Chemistry, 2010)
A new Schiff base complex has been synthesized and characterized by elemental analyses, IR and molar conductance. Thermodecomposition kinetics of the complex were investigated under non-isothermal condition. TG and DTG curves indicate the complex decomposes in three steps. The kinetics of step(1) and (3) were calculated by a combination of Achar differential and Coats-Redfern integral methods. The kinetic equations may be expressed as: step (1): dα/dt = Ae–E/RT (1-α)2; step (3): dα/dt = Ae–E/RT /2(1-α)3.